Faktor-Faktor Yang Mempengaruhi Audit Delay (Study pada Perusahaan Food and Beverages di Bursa Efek Indonesia 2018-2020) - Yuliana Afifah (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2022)
Public companies are required to publish financial statements in time that has been set by the OJK which is lees than 120 days. The delay of the company in the publish financial statements to give effect to the good name of the company and the trust investor that can make declining investor confidence to the company. One of the companies that experienced a delay in the publishing of financial statements Food and Beverages Companies on the IDX in 2018-2020. Purpose of the study is determine of the factors that effect audit delay. Data analysis in this study used the logistic regression method. The results of this study indicate that company size has no effect on audit delay in food and beverages companies on the IDX 2018-2020, leverage does not affect audit delay on food and beverages companies on the IDX 2018-2020, KAP size does not affect audit delay on food companies. and beverages on the IDX 2018-2020, and the auditor's opinion has an effect on audit delay in food and beverages companies on the IDX 2018-2020. Keywords: Firm Size; Leverage; KAP Size; Auditor Opinion; Audit Delay